The Effectiveness of Health Education to Enhance Community Perception and Preferences Towards Honey for Healthcare - Aris Widiyanto; Joel Rey Acob Acob; Rita Benya Adriani; Tri Yuniarti; Trisakti Halimah; Joko Tri Atmojo (Public Health of Indonesia)
Background: Understanding the health benefits of honey has the potential to influence individual and family decision-making related to wellness and healthcare. Enhancing public knowledge through structured health education is therefore essential in shaping positive attitudes and informed choices regarding natural health remedies, such as honey.